The Effect of Gender and Gender Match on Mortality in Pediatric Heart Transplantation. Issue 11 (1st October 2013) - Tosi, L.; Federman, M.; Markovic, D.; Harrison, R.; Halnon, N. J.
Abstract : The effect of organ–recipient gender match on pediatric heart transplant mortality is unknown. We analyzed the effects of gender and donor–recipient gender matching. Based on Organ Procurement and Transplant Network data, we performed a historical cohort study in a population of 3630 heart transplant recipients less than 18 years old. We compared unadjusted and adjusted mortality by recipient gender, donor gender and between gender‐matched and gender‐mismatched recipients. Female recipients had decreased survival compared to male recipients (unadjusted hazard ratio [HR] 1.16, confidence interval [CI] 1.02–1.31; p = 0.020). Organ–recipient gender mismatch did not affect mortality for either male or female recipients, though gender‐mismatched females had the worst survival compared to gender‐matched males, who had the best survival (unadjusted HR 1.26, CI 1.07–1.49; p = 0.005). After adjustment for other risk factors affecting transplant mortality, female recipients had decreased survival compared to male recipients (HR 1.27, CI 1.12–1.44; p = 0.020) and gender matching had no effect. In conclusion, gender mismatch alone did not increase long‐term mortality for pediatric heart transplant recipients. However, there may be additive effects of gender and gender matching affecting survival. There are insufficient data at this time to support that recipient and donor gender should affect heart allocation in children. Abstract : The authors find that female gender is associated with increased mortality among pediatric heart transplant recipients while donor‐recipient gender match poses no survival advantage.